Sport-specific limb prostheses in para sport - Grobler, L.; Derman, W. (Physical Medicine & Rehabilitation Clinics of North America, 2018)
Prostheses form an essential part of participation in sport and physical activity for athletes with lower or upper limb amputation. These prostheses come in the form of everyday nonsport-specific prostheses, as well as sport-specific prostheses designed to enable participation in specific sports. Sport-specific prostheses are designed to the requirements of the sport to facilitate the achievement of peak performance without causing significant risk of injury. This article addresses the various factors associated with participation in sport and physical activity for individuals with amputation, including the various prostheses for upper and lower limbs and prostheses for different sports.